Navigation Strategy with Multi-Robots in Confined Environments to Improve Radio Signal Coverage - Campos, Sofia Pereira; Cid, André Luiz Maciel; Vangasse, Arthur Da Costa; Júnior, Gilmar; Baião, João; Pimenta, Luciano; Barros, Luiz; Pessin, Gustavo; Freitas, Gustavo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Safely performing tasks in confined environments poses significant risks, often necessitating the use of mobile robots. However, one of the major challenges associated with utilizing mobile robots in these tasks is establishing effective communication between them, typically achieved through radios with limited coverage. To optimize radio signal coverage within such environments, this paper introduces a multi-robot navigation strategy. This strategy ensures a direct line of sight between radios, thereby enhancing communication during teleoperation. The effectiveness of the proposed strategy is evaluated through simulations conducted in CoppeliaSim and validated through a proof-of-concept experiment. Preliminary results are promising, highlighting a significant surge in radio signal coverage within confined environments, achieving an improvement of over 50% in the distance covered during inspection activities using mobile robots, thus facilitating the execution of tasks safely in previously inaccessible regions.